2008
DOI: 10.1063/1.3020223
|View full text |Cite
|
Sign up to set email alerts
|

Living tissue under treatment of cold plasma atmospheric jet

Abstract: The interaction of the cold atmospheric plasma jet with fibroblast cells was studied. Plasma jet was initiated in the helium flow blowing through the syringe by application of high ac voltage to the discharge electrodes. The plasma jet had a length of 5cm and a diameter of 1.5–2mm in ambient air. Treatment of cells with plasma jet resulted in decreasing of cell migration rate, cell detachment, and appearance of “frozen” cells, while treatment with helium flow (no plasma) resulted in appearance of frozen cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
164
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(172 citation statements)
references
References 13 publications
5
164
0
3
Order By: Relevance
“…Studies investigating the interaction of plasma jets with living cells have shown eradication of pathogens (Goree et al, 2006;Kolb et al, 2008;Stoffels et al, 2006), blood coagulation Kalghatgi et al, 2007;Kieft et al, 2005), tissue sterilization Shashurin et al, 2008), and the ablation of cultured liver cancer cells (Zhang et al, 2008). The effects of cold atmospheric plasma were shown to be due not to heat, but to active species, mainly oxygen/hydroxyl radicals and nitric oxide, generated in the plasma or in the tissue brought into contact with the plasma (Chen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies investigating the interaction of plasma jets with living cells have shown eradication of pathogens (Goree et al, 2006;Kolb et al, 2008;Stoffels et al, 2006), blood coagulation Kalghatgi et al, 2007;Kieft et al, 2005), tissue sterilization Shashurin et al, 2008), and the ablation of cultured liver cancer cells (Zhang et al, 2008). The effects of cold atmospheric plasma were shown to be due not to heat, but to active species, mainly oxygen/hydroxyl radicals and nitric oxide, generated in the plasma or in the tissue brought into contact with the plasma (Chen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Generation of atmospheric plasmas is not restricted to the gas phase: a well-known type is an underwater corona discharge, which has attracted much attention as a cheap and environmentally safe means for cleaning polluted water (Hoeben et al, 2000). In addition, a vacuum system is not required for cold plasma, making it possible to use in nanotechnology and biomedicine applications (Shashurin et al, 2008). Plasma became commercially available for medical use in the 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown by several groups that the plasma is able to induce death (the programmed death, apoptosis or the necrotic cell rupture) in a number of cancer cell types. [3][4][5][6][7][8][9][10][11][18][19][20][21] Among these, the induction of apoptosis by plasma treatment has proven an intriguing issue. The ROS produced by plasma are considered to be the key constituents that induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…3,4,[18][19][20][21] Of particular interest are the plasma interactions with cancerous cells. It has been shown by several groups that the plasma is able to induce death (the programmed death, apoptosis or the necrotic cell rupture) in a number of cancer cell types.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Compared with the dielectric barrier discharge (DBD) jet powered by kHz, the RF APGD plasma jet decays rapidly after injecting from the generator nozzle, due to the weak electrical field in the jet region. 6 And the materials which would be processed are usually located at about 2 mm downstream the exit of the plasma generator to keep treating effect with enough active species.…”
Section: Introductionmentioning
confidence: 99%